2018
DOI: 10.1055/s-0038-1660771
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Implications of Innervation Pattern of the Triceps Muscle: A Cadaveric Study

Abstract: The innervation pattern of triceps is complex and not fully comprehended. Anomalous innervations of triceps have been described by various authors. We have attempted to delineate the nerve supply of the triceps and documented the anomalous innervations of its different heads. The brachial plexus and its major branches (in the region of the axilla and arm) and triceps were dissected in 36 embalmed cadaver upper limbs. Long head received one branch from radial nerve in 31 (86%) specimens. Four (11%) specimens re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…Al-Meshal and Gilbert 12 observed dual innervation of the triceps long head in 2 of their 22 specimens. Contrary to other studies, 13,14 we were unable to identify the triceps long head motor branch stemming from the axillary nerve or posterior cord. In studies by de Sèze et al, 15 the triceps long head was never innervated by the radial nerve.…”
Section: Discussioncontrasting
confidence: 99%
“…Al-Meshal and Gilbert 12 observed dual innervation of the triceps long head in 2 of their 22 specimens. Contrary to other studies, 13,14 we were unable to identify the triceps long head motor branch stemming from the axillary nerve or posterior cord. In studies by de Sèze et al, 15 the triceps long head was never innervated by the radial nerve.…”
Section: Discussioncontrasting
confidence: 99%
“…The cadaveric study shed some light to increase the safety and the utility of this approach; 1- It is better to leave 2 cm at least from superior margin during anconeus incision as the present cadaveric study (in twelve specimens) showed connection between the medial head of the triceps and anconeus. Also, it could be at risk in cutting the nerve to anconeus because it branches from the radial nerve of the medial head of triceps at the anconeus superior margin [ 17 ]. 2- It is better to plan splitting of the anconeus muscle in the medial 2/3 of the middle segment.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is important to have the knowledge about anatomical variations in the innervation of triceps brachii. This will prevent inadvertent iatrogenic injury and also provides new modalities for the free functional nerve and muscle transfers for the triceps brachii (11). Ulnar collateral nerve (UCN) runs along with the UN, but it is a branch of RN (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%